Der Wille zum Subjekt : Zur Genealogie politischer Inklusion in Frankreich (16.-20. Jahrhundert) - Otto, Marcus (2014)
Marcus Otto undertakes a systems theory inspired genealogical rewriting of a metanarrative of modernity, which unfolds as a political inclusion-imperative of historic potency on the subject figure. This implies the deconstruction of an overarching will to be the subject which predominates not only in political and societal self-descriptions, but also in historiography to this day. This results in a »failure to decapitate the king,« as Foucault once put it, with reference to political thought.